Book Review: Timmer, C. Peter. 2015: Food Security and Scarcity. (April 2018) - Alfranca, Oscar
Timmer, C. Peter. 2015: Food Security and Scarcity . Philadelphia: University of Pennsylvania Press. 240 pp. £39. ISBN: 9780812246667.